2017
DOI: 10.1016/j.compstruct.2017.07.029
|View full text |Cite
|
Sign up to set email alerts
|

A model to analyse deformations and stresses in structural batteries due to electrode expansions

Abstract: A model to analyse deformations and stresses in structural batteries due to electrode expansions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…Xu et al [15,16] have developed a numerical framework using a Multiphysics FE-model to study how the internal stresses in 3D structural batteries are affected by volume change of constituents. Moreover, Dionisi et al [17] developed an analytical model to predict deformations and stresses in laminated structural batteries due to volume change of the active materials. Several studies have though shown that the developed stresses in lithium ion batteries are highly dependent on generated heat and temperature inside the cell.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Xu et al [15,16] have developed a numerical framework using a Multiphysics FE-model to study how the internal stresses in 3D structural batteries are affected by volume change of constituents. Moreover, Dionisi et al [17] developed an analytical model to predict deformations and stresses in laminated structural batteries due to volume change of the active materials. Several studies have though shown that the developed stresses in lithium ion batteries are highly dependent on generated heat and temperature inside the cell.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…By using carbon ber as a conductive and structural current collector backbone of the device, which displaces Al and Cu metals, a reduction of up to 15% of the gravimetric footprint of Li-ion batteries is achieved, which is advantageous for offsetting the mass penalty of incorporating battery systems in composites. 49 While some past work has considered carbon ber as an electrode itself, lower capacity and the electrochemical cycling reversibility of Li [35][36][37] combined with structural degradation to the composite backbone during successive charge/discharge cycles make graphite coated onto a carbon ber electrode a more practical selection for a high performance and stable structural battery design. This design incorporating graphite anodes and lithium iron phosphate cathodes (GR|LFP) is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[24][25][26][27] However, it is notable that this approach results in no gravimetric advantage for the system compared to simply just externally connecting the battery, and can result in a mechanical disadvantage for the composite at the battery packaging/epoxy interface. With this said, only recently have approaches been demonstrated for direct integration of battery materials into structural composites, but these approaches so far have demonstrated negligibly low energy density relative to the total mass of combined active and composite materials with moderate cycling stability [28][29][30][31][32][33][34][35][36][37] or moderate energy density and low cycling stability. 38 Outside of structural batteries, it is known that surfaces and interfaces are critical to achieve stable, high performance energy storage.…”
Section: Introductionmentioning
confidence: 99%
“…Johanna Xu et al [18,19] developed a framework in COMSOL for multiphysics modelling of the 3D structural battery to predict internal stresses due to swelling/shrinkage of the constituents related to the electrochemical reactions. Furthermore, an analytical model to predict the deformations and stresses in laminated structural batteries has been developed by Dionisi et al [20]. In contrast to ordinary batteries, the active materials in the structural battery are intended to carry mechanical load.…”
Section: Accepted Manuscriptmentioning
confidence: 99%